2020
DOI: 10.1111/gcb.14992
|View full text |Cite
|
Sign up to set email alerts
|

Extending the range of applicability of the semi‐empirical ecosystem flux model PRELES for varying forest types and climate

Abstract: Applications of ecosystem flux models on large geographical scales are often limited by model complexity and data availability. Here we calibrated and evaluated a semiempirical ecosystem flux model, PREdict Light-use efficiency, Evapotranspiration and Soil water (PRELES), for various forest types and climate conditions, based on eddy covariance data from 55 sites. A Bayesian approach was adopted for model calibration and uncertainty quantification. We applied the site-specific calibrations and multisite calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 74 publications
5
40
6
Order By: Relevance
“…However, a positive N‐fertilization effect on GPP was not always observed. At our site, previous studies showed no effect of N supply on GPP when measured from biometrics (Lim et al, 2015) or shoot‐scale gas exchange (Tarvainen, Lutz, Räntfors, Näsholm, & Wallin, 2016), but Tian et al (2020), who used EC data to parametrize a model, did find higher GPP in the fertilized plot than in the reference plot. Thus, the GPP results have been mixed, depending on which method was used.…”
Section: Introductioncontrasting
confidence: 53%
See 4 more Smart Citations
“…However, a positive N‐fertilization effect on GPP was not always observed. At our site, previous studies showed no effect of N supply on GPP when measured from biometrics (Lim et al, 2015) or shoot‐scale gas exchange (Tarvainen, Lutz, Räntfors, Näsholm, & Wallin, 2016), but Tian et al (2020), who used EC data to parametrize a model, did find higher GPP in the fertilized plot than in the reference plot. Thus, the GPP results have been mixed, depending on which method was used.…”
Section: Introductioncontrasting
confidence: 53%
“…Using Bayesian calibration, we adjusted parameters of PRELES according to their ability to reproduce EC observations (Tian et al, 2020). The Bayesian framework treated all terms in the model calibrations and predictions as probability distributions (Clark, 2007; Dietze, 2017).…”
Section: Statisticsmentioning
confidence: 99%
See 3 more Smart Citations